Advancing real-time pH sensing capabilities to monitor coastal acidification as measured in a productive and dynamic estuary (Ría de Arousa, NW Spain) - Velo, Anton; Padin, Xose Antonio (Frontiers in Marine Science, 2022)
Ocean acidification has critical impacts on marine ecosystems, but presents knowledge gaps on the ecological impacts requiring large-scale monitoring of physicochemical conditions to predict biological responses to ocean pH projections. The threat is especially significant in coastal regions like upwelling areas which are more sensitive and appear to respond more rapidly to anthropogenic perturbations. These ecosystems, such as the northwest coast of the Iberian Peninsula are characterized by complex physical and biogeochemical interactions, supporting enormous biological productivity and productive fisheries. The distribution of pH in upwelling systems has high variability on short temporal and spatial scales preventing a complete picture of acidification, which exhibit long-term pH rates markedly different from the measured in open waters. This motivation to significantly expand the coverage of pH monitoring in coastal areas has driven us to develop an autonomous pH monitoring instrument (from now on SURCOM) based on the Honeywell Durafet® pH electrode. A relevant feature is that SURCOM transmits near real-time pH and temperature measurements every 10.5 min through SIGFOX®, a low-power, low-bandwidth network for data transmission. This very careful design allows us to achieve a very low power consumption for the complete system resulting in 3 years of full autonomy with no other need than external cleaning and calibration. In this paper we describe the setup and the data set obtained by a SURCOM instrument over 240 days in a highly productive and dynamic coastal ecosystem, the Ría de Arousa embayment, providing valuable information on the performance of these low-cost and highly stable sensors, with potential for improving the pH variability description in nearshore systems and for reinforcing the monitoring-modeling of coastal acidification.